A descriptive analysis of primary care providers' interest in clinical pharmacy services - Belyin Gutierrez Euceda; Stefanie P. Ferreri; Lori T. Armistead (Elsevier, 2023)
Background: Various clinical pharmacy services exist to improve the health outcomes of patients. However, there are numerous barriers to their implementation and execution, especially in outpatient settings. As pharmacists design and implement clinical pharmacy services in outpatient settings, they often do not consider the needs of providers until after service development. Objectives: The purpose of this study was to assess primary care providers' (PCPs') perceptions of clinical pharmacy services and their clinical pharmacy support needs. Methods: A web-based survey was distributed via email to PCPs across North Carolina (NC). Survey dissemination was completed in two phases. Data analysis consisted of mixed methods - quantitative and qualitative. Descriptive statistics were used to analyze demographic differences within each phase as well as the ranking of medication classes/disease states by providers. Qualitative data analysis through inductive coding was done to assess provider perceptions of clinical pharmacy services. Results: The response rate of the survey was 19.7%. Providers with previous experience with a clinical pharmacist rated overall services as positive. 62.9% of PCPs (N = 80) provided their perception of the positive attributes (pros) of clinical pharmacy services. 53.5% of PCPs (N = 68) provided their perception of the negative attributes (cons) of clinical pharmacy services. The top three medication classes/disease states that providers indicated they would value clinical pharmacy services for were: comprehensive medication management (CMM), diabetes medication management, and anticoagulation medication management. Of the remaining areas assessed, statin and steroid management ranked the lowest. Conclusions: The results from this study demonstrated that clinical pharmacy services are valued by PCPs. They also highlighted how pharmacists can best contribute to collaborative care in outpatient settings. As pharmacists, we should aim to implement the clinical pharmacy services that PCPs would value most.